A Multi-Objective Distribution System Expansion Planning Incorporating Customer Choices on Reliability - Mazhari, Seyed Mahdi (2016)
This paper proposes a new multi-objective framework for primary distribution system planning (DSP). Further consideration is devoted to early DSP formulations in order to assess the risk imposed by probabilistic customer choices on reliability (CCOR). The CCOR is a buy/sell strategy that permits customers to pay the electricity price equiponderant to the reliability level provided by the distribution utility over the contract period. A Monte Carlo-based simulation is carried out to examine the effects of the probability of a customer's interest in adopting the CCOR on profit-at-risk. Furthermore, the DSP was conducted to simultaneously minimize both total planning cost and profit-at-risk. The resultant optimization problem is solved through the non-dominated sorting genetic algorithm (NSGA-II) accompanied by a fuzzy decision making method to select the best result among the obtained Pareto optimal set of solutions. The developed method is applied to an actual large-scale distribution system with about 140\thinspace000 customers, followed by a discussion on results.